Time Course of Peripheral Leukocytosis and Clinical Outcomes After Aneurysmal Subarachnoid Hemorrhage - Gusdon, Aaron M.; Savarraj, Jude P. J.; Shihabeddin, Eyad; Paz, Atzhiry; Assing, Andres; Ko, Sang-Bae; McCullough, Louise D.; Choi, Huimahn Alex (Frontiers in Neurology, 2021)
Objective: Systemic inflammation after subarachnoid hemorrhage (SAH) is implicated in delayed cerebral ischemia (DCI) and adverse clinical outcomes. We hypothesize that early changes in peripheral leukocytes will be associated with outcomes after SAH. Methods: SAH patients admitted between January 2009 and December 2016 were enrolled into a prospective observational study and were assessed for Hunt Hess Scale (HHS) at admission, DCI, and modified Ranked Scale (mRS) at discharge. Total white blood cell (WBC) counts and each component of the differential cell count were determined on the day of admission (day 0) to 8 days after bleed (day 8). Global cerebral edema (GCE) was assessed on admission CT, and presence of any infection was determined. Statistical tests included student's t-test, Chi-square test, and multivariate logistic regression (MLR) models. Results: A total of 451 subjects were analyzed. Total WBCs and neutrophils decreased initially reaching a minimum at day 4–5 after SAH. Monocyte count increased gradually after SAH and peaked between day 6–8, while basophils and lymphocytes decreased initially from day 0 to 1 and steadily increased thereafter. Neutrophil to lymphocyte ratio (NLR) reached a peak on day 1 and decreased thereafter. WBCs, neutrophils, monocytes, and NLR were higher in patients with DCI and poor functional outcomes. WBCs, neutrophils, and NLR were higher in subjects who developed infections. In MLR models, neutrophils and monocytes were associated with DCI and worse functional outcomes, while NLR was only associated with worse functional outcomes. Occurrence of infection was associated with poor outcome. Neutrophils and NLR were associated with infection, while monocytes were not. Monocytes were higher in males, and ROC curve analysis revealed improved ability of monocytes to predict DCI and poor functional outcomes in male subjects. Conclusions: Monocytosis was associated with DCI and poor functional outcomes after SAH. The association between neutrophils and NLR and infection may impact outcomes. Early elevation in monocytes had an improved ability to predict DCI and poor functional outcomes in males, which was independent of the occurrence of infection.